E-Commerce Design for Palembang Home Tailors - Irma Salamah; Ciksadan Ciksadan; Riska Melyani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
Home tailors are SMEs that are business opportunities that are usually chosen by housewives because, being a home tailor can be a solution for housewives to keep earning even though they are at home. The problems faced are in marketing and promoting home tailoring services because usually the target customers are only the surrounding environment, therefore innovation in promotion strategies is needed, the use of modern technology such as E-Commerce can be a strategy in business, so that it can be known to the wider community. Responsive Web-based E-Commerce design for ordering and purchasing information systems in increasing the income of home-tailor SMEs, to design this information system The programming language that will be used is PHP, and MySql as a database.